The Effectiveness of Gamisafe Sexual Harrasment Application on Elementary School Students' Understanding - Khotimah, Khusnul; Fadhilah, Ayu (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to determine and measure the effectiveness of gamification-based learning applications, namely gamisafe sexual harrasment. This study focuses on elementary school students' understanding of sexual education. Methodology:.This study used a quantitative approach with a one-group pretest-posttest type of pseudo-experimental design. The research subjects were 59 grade 4 elementary school students. Data were collected through comprehension test instruments given before (pretest) and after (posttest) students used the gamisafe sexual harassment application. after the data were collected, the data were then processed using spss version 26. Main Findings: The use of gamisafe sexual harassment application is proven to be effective in improving students' understanding of sexual education. This is based on the scores obtained by students where after descriptive statistical tests were carried out, the average difference between pretest and posttest scores was 13.3898. The difference between the minimum value of the post-test and the minimum value of the pre-test is a difference of 24. In the T test results, it was found that the significance value was 0.000, which can be said that there is significance in using the gamisafe sexual harassment application Novelty/Originality of this study: The novelty in this research is that the gamisafe sexual harassment application is designed using features that are fun for users. The first is the interactive material feature. Then, there are daily quizzes. There is a role-playing feature where students can choose what actions to take when facing sexual harassment.